Workers, workplaces, sorting, and wage dispersion in Mexico - Jorge Pérez Pérez; José G. Nu\~no-Ledesma (Banco de México, 2024)
Between 2004 and 2018, the spread of wages in Mexico's private labor sector remained stable. Nonetheless, the underlying factors behind salary dispersion underwent significant shifts. To uncover these changes, we analyze an employer-employee dataset comprising the near-universe of Mexico's formal employment. We estimate log wage models and decompose earnings dispersions into worker, workplace and sorting components. At the national level, we find that sorting increased its importance over time. While worker-level factors were the main contributors to salary variability in the 2004-2008 period, workplace factors became as important as worker-level factors in the 2014-2018 time segment. The influence of workplace factors on wage dispersion correlates negatively with per capita GDP at the regional level.
Keywords: J21; J31; R23; O15; O54; 330; Assortative matching; regional development; wage dispersion; workplace wage premia